Peningkatan Keselamatan dan Kesehatan Kerja (K3) melalui Sosialisasi Alat Pelindung Diri (APD) kepada Pekerja Konstruksi (Lokasi: Renovasi Gedung Perpustakaan Politeknik Penerbangan Palembang) - Viktor Suryan; Anggi Nidya Sari; Direstu Amalia; Virma Septiani; Herlina Febiyanti (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2020)
The awareness of Occupational Health and Safety (OHS) to Increase working productivity. There are many cases caused the human error and disregard the standard operational procedure related to OHS. This accident may decline of efficiency due to unexpected operational cost. This issues also affect the inefficiency and ineffectively working circumstances. Furthermore, construction project is one of the highest of risk of accident such OHS. Also, this community service activity encourages the awareness of OHS in construction project. This activity target is library construction’s labors in Palembang Aviation Polytechnic. However, it is not limited to workers, this action involves the owners, managers, and supervisors to commit to OHS. The result is to escalating the understanding of OHS procedure in particularly personal protective equipment.